Argumentasi Analogis Siswa SMP Dalam Menyelesaikan Masalah Matematika Ditinjau Dari Perbedaan Jenis Kelamin - Lieska Maulita Shamimi; Abdul Haris Rosyidi (MATHEdunesa, 2021)
Analogical argumentation is a part of analogical reasoning which has an important role in mathematics. Analogical argumentation can help one to demonstrate that a statement is reasonable. Someone's argument can be seen when solving a problem because argumentation functions to generate and support a solution to a problem. In solving problems, gender influences the process. This qualitative research aims to describe students' analogical argumentation in solving math problems in terms of gender differences. The subjects of this study were two students from class VIII-K SMP Negeri 2 Surabaya, one male and one female with the same math ability. The research was conducted online via googleform for the analogical argumentation test and whatsapp as a platform for interviews. The research instruments were the analogical argumentation test and the latest interviews. The data obtained were then analyzed using analogical argumentation components, namely classification and conclusions. The results showed that there were complaints on the classification component, namely that the two students were able to identify the characteristics or structure of the source problem and the target problem so that the comments component was able to make a statement of the solution. The difference is in the classification component, namely students who are able to identify the problem between the problem and the target problem, not quite right in the understanding of the structure. Both female students were able to use analogical argumentation to conclude both problems logically, while male students were less logical.